2017
DOI: 10.1021/acsami.7b03346
|View full text |Cite
|
Sign up to set email alerts
|

Green, Water-Dispersible Photoluminescent On–Off–On Probe for Selective Detection of Fluoride Ions

Abstract: Considering the high toxicity and widespread availability of fluoride ions in different environmental matrices, it is imperative to design a probe for its detection. In view of this, a selective fluorescent on-off-on probe based on carbon quantum dots (CQDs) and Eu has been designed. We have synthesized water-soluble carboxylic acid-functionalized CQDs and monitored their interaction with Eu. Luminescence quenching in the CQD emission was observed (switch-off) on adding Eu ions. We investigate the reason for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(33 citation statements)
references
References 60 publications
0
33
0
Order By: Relevance
“…The relative standard deviation (RSD) of uorescence intensities without F À and those containing mM F À , which were detected in parallel for 11 consecutive times, was 3.1%. The detection limit of this method was lower than that of uorescence method, 25,52,53 approximating to that of absorbance method 54 ( Table 1). In comparison with general uorescence methods for organic small molecules based on "Turning on" pattern, 52,53 this detection system can not only realize uorescence analysis and detection of uorine ions under "Turning on-off" pattern, but also improve the selectivity of uorescence detection of AIE-based organic molecules.…”
Section: F à Detection By the Tpe-cooh/al 3+ Systemmentioning
confidence: 72%
See 1 more Smart Citation
“…The relative standard deviation (RSD) of uorescence intensities without F À and those containing mM F À , which were detected in parallel for 11 consecutive times, was 3.1%. The detection limit of this method was lower than that of uorescence method, 25,52,53 approximating to that of absorbance method 54 ( Table 1). In comparison with general uorescence methods for organic small molecules based on "Turning on" pattern, 52,53 this detection system can not only realize uorescence analysis and detection of uorine ions under "Turning on-off" pattern, but also improve the selectivity of uorescence detection of AIE-based organic molecules.…”
Section: F à Detection By the Tpe-cooh/al 3+ Systemmentioning
confidence: 72%
“…[12][13][14][15][16][17][18][19][20][21] In recent years, aggregation-induced emission (AIE) materials have attracted high attention from researchers. 13,15,19,[22][23][24][25][26][27][28][29] No matter AIE materials emit weak uorescence or don't emit uorescent under dissolved state, the uorescence will be obviously enhanced under aggregation state. 16,23,24,28,30 AIE phenomenon has been applied to various elds, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…31 The detection of rare earth elements with C-dots has been relatively less reported. Singhal et al used Eu-coordinated Cdots to detect F À ions, 33 and indicated that the Eu 3+ ions interacted relatively loosely with the carboxylic acid moiety on the C-dots. Kailasa et al recently reported that Eu 3+ hybrid Cdots could be used as a uorescent nanosensor to detect Hg 2+ ions, 34 but in their sensor the Eu 3+ ions did not directly coordinate with the C-dots.…”
Section: Introductionmentioning
confidence: 99%
“…For fluoride ion (F − ), the smallest size and highest charge density, any chronic deficiency of F − will lead to gastric and kidney disorder or osteoporosis, while excess F − would induce dental and skeletal fluorosis and other serious diseases including collagen breakdown, bone disorders and immune system disruption . Great efforts have been devoted for F − detection, such as chromatography, electrochemistry, photoluminescence, mass spectrometry,, fluorescent spectrophotometry and colorimetric spectrophotometry . For example, Bhosale, et al .…”
Section: Introductionmentioning
confidence: 99%